Petrović-Type Inequalities for Harmonic h-convex Functions. (8th January 2020) - Abbas Baloch, Imran; Chu, Yu-Ming
Abstract : In the article, we establish several Petrović-type inequalities for the harmonic h -convex (concave) function if h is a submultiplicative (super-multiplicative) function, provide some new majorizaton type inequalities for harmonic convex function, and prove the superadditivity, subadditivity, linearity, and monotonicity properties for the functionals derived from the Petrović type inequalities.